1995
DOI: 10.1007/bf00300021
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and age-related composition of 10 617 calculi analyzed by infrared spectroscopy

Abstract: A series of 10 617 calculi were analyzed by stereomicroscopy and infrared spectroscopy. This first study of French calculi was compared with large series in the literature. That the frequency of pure calculi was the lowest ever observed can be related to the methodology routinely used in our laboratory, which includes microsampling. We described more than 70 components among the 10 617 calculi. The overall sex ratio male to female patients was high (2.27) and increased over the period 1981-1993. Calcium oxalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
2
7

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(113 citation statements)
references
References 21 publications
7
95
2
7
Order By: Relevance
“…Urinary calculi made of calcium oxalate monohydrate (COM) are among the most common stones affecting the populations of industrialized countries [1,2], and can be especially resistant to shock wave (SW) lithotripsy [3,4]. However, study of stone breakage in vitro has shown that COM stones vary dramatically in their fragility to SW's, with some stones being very resistant, and others quite fragile [5,6], and this variability is consistent with clinical experience [4].…”
Section: Introductionsupporting
confidence: 52%
“…Urinary calculi made of calcium oxalate monohydrate (COM) are among the most common stones affecting the populations of industrialized countries [1,2], and can be especially resistant to shock wave (SW) lithotripsy [3,4]. However, study of stone breakage in vitro has shown that COM stones vary dramatically in their fragility to SW's, with some stones being very resistant, and others quite fragile [5,6], and this variability is consistent with clinical experience [4].…”
Section: Introductionsupporting
confidence: 52%
“…However, micro-CT revealed visible content of other minerals in many of the stones; this is expected, because most stones contain more than one mineral component (18). In particular, micro-CT revealed calcium salt content in 13 of the 16 uric acid stones.…”
Section: Resultsmentioning
confidence: 84%
“…Few stones are composed of a single material. 17 Given the variability of stone densities within the same stone, 18 we determined the mean stone density of three separate readings within the same stone. The results of our study show that a mean stone density ≥800 HU is a predictor of ESWL failure.…”
Section: Discussionmentioning
confidence: 99%